Does Corporate Social Responsibility Affect Stock Returns? - Scott (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2022)
Introduction: This paper finds that U.S. firms with higher corporate social responsibility (CSR) compliance levels have higher stock returns from 2006 to 2014. This result is robust after controlling for size, book to market ratio, momentum, etc Purpose: There appears to be a positive relationship between corporate social responsibility compliance level and product market competition level. Methodology: Obtain CSR data from Global Reporting Initiative. Monthly stock return files and annual firm fundamentals are downloaded from CRSP and Compustat database. In the GRI dataset, we quantify firm’s compliance level as numeric values from 0 to 5, with 5 being the highest compliance level. The compliance level score mapping is displayed in Table 1 in the appendix. Findings: This paper finds that engagement in CSR activities have a positive impact on stock returns. This effect is robust after controlling for firm characteristics such as size, book to market equity ratio.